QUALITY OF LIFE OF THE ELDERLY IN THE CITY OF BUCARAMANGA: A POPULATION-BASED STUDY. - Mejia Blanquicet, Pedro Antonio
The ageing of the world's population is an intrinsic process that generates relevant socio-demographic changes; And although old age should not be considered synonymous with illness, there are factors such as inadequate lifestyles, stress, excessive workload, polypharmacy and underlying diseases, among others That manage to affect the emotional and functional state of the elderly, This article evidences results on the perception of the quality of life of the elderly person in the city of Bucaramanga related to sociodemographic variables (sex, age groups, marital status, educational level, health affiliation regime, type of housing and physical activity) and in this way present results that can build better public policies for the benefit of the aforementioned population Population Objective : To describe the quality of life of adults in the city of Bucaramanga. Methodology: a quantitative analytical approach, as it is carried out through the application of statistical knowledge considering the hypothesis and variables. Such objective measurements and statistical analyses of the secondary data collected through surveys will be interpreted by means of initial predictions (hypotheses) and previous studies (theory). Then, the variables were described and analyzed and their relationship with the variable quality of life in the elderly in the city of Bucaramanga will be analyzed